(untitled) (Swiss Medical Weekly, 2012)
QUESTION UNDER STUDY: To determine the incidence and determinants of tick related diseases in Switzerland, such as tick bites and Lyme borreliosis in primary care and tick borne encephalitis. METHODS: Analysis of the Swiss data collected by mandatory and facultative surveillance systems for the reporting period of 2008 to 2011. RESULTS: Tick related diseases in Switzerland are common. About 17,000 to 23,000 estimated cases of tick bites lead to a consultation (yearly incidence 254 per 100,000 inhabitants); about 7,000 to 12,000 estimated cases of Lyme borreliosis (yearly incidence 131 per 100,000 inhabitants) and 98 to 172 cases of tick borne encephalitis occur each year (yearly incidence 1.6 per 100,000 inhabitants). The most affected area is the north-eastern part of Switzerland. Whereas cases of tick borne encephalitis are restricted to local endemic areas, cases of Lyme borreliosis and tick bites are spread all over Switzerland. CONCLUSIONS: Tick related diseases are frequent and widespread in Switzerland. They are leading to a considerable usage of the health care system. Thus, tick bite prevention and vaccination against tick borne encephalitis are essential. However, long term follow-up cohort studies with reasonably large study populations after tick bite would be required to elucidate the risk of developing a tick borne disease.